Controlling banana bunchy top disease in Benin: crop protection strategies with socio-economic perspectives - Retkute, R.; Zandjanakou-Tachin, M.; Omondi, B.A.; Agoi, U.R.; Vodounou, Y.M.; Akofodji, H.; Akpla, E.; Dossou, L.; Medenou, E.; Etchiha, A.; Attadeou, A.; Kumar, P.L.; et al. (2025)
Societal Impact Statement Banana and plantain are vital for food security and income in West Africa, yet banana bunchy top virus (BBTV) threatens production. This study combined remote sensing, field surveys, modelling and socio-economic analysis to assess BBTV spread and control strategies in Benin. We found that risk is highest in southern regions with low disease awareness, limited adoption of control measures and widespread informal planting material exchange. By identifying priority areas and context-specific interventions, our findings provide actionable guidance for targeted BBTV management, supporting smallholder resilience, reducing disease impact and safeguarding livelihoods across sub-Saharan Africa.